Environmental Enrichment for Pig welfare during Transport - Crone, Carla; Caldara, Fabiana Ribeiro; Martins, Renata; de Oliveira, Geyssane Farias [UNESP]; Marcon, Adila Vasconcelos; Garcia, Rodrigo Garófallo; dos Santos, Luan Sousa [UNESP]; Almeida Paz, Ibiara Correia Lima [UNESP]; Lippi, Isabella Cristina De Castro [UNESP]; Burbarelli, Maria Fernanda de Castro (Taylor & Francis, 2021)
This study aimed to assess the effects of environmental enrichment for pigs during transportation in different phases of their productive cycle. Two trials were conducted, the first during transportation of pigs from the piglet production unit (PPU) to the nursery (n = 250) and the second during the transportation of nonhuman animals from the finishing unit (FU) to the slaughterhouse (n = 120). This work was an observational study with five environmental enrichments: Control–no enrichment; object–use of enrichment objects in the truck; aroma–use of lavender aroma in the truck; music–music in the truck; and vehicle sound. Animal behavior during transportation, respiratory rate, skin surface temperature, and skin lesion score were assessed. Piglets from the treatment music had the lowest frequency of agonistic behaviors during transportation from the farrowing to the nursery and lower skin temperature after transportation. Piglets from the control had the highest respiratory rate prior to transportation. Pigs familiarized with vehicle noises spent most of their time lying during the trip to the slaughterhouse. The creation of a familiar environment to pigs seems promising in enhancing animal well-being during transportation.
Keywords: Aromatherapy; familiarity; music therapy; sensory enrichment; welfare